Recovery of high purity plumbagin from Drosera intermedia - Grevenstuk, Tomás (2013)
In this study a simple process encompassing an efficient extraction and fractionation method to obtain high purity plumbagin from micropropagated D. intermedia plants is described. Plumbagin is a naphthoquinone derived from a diverse but restricted group of plant species that includes the Drosera spp. and is in demand for pharmacological research. It was brought initially to the attention of researchers due to its broad antimicrobial and antitumor properties but has continued to find application against new pharmacological targets. The procedure described in this work involved testing four extraction methods to maximize product recovery and separating the 30–50% acetonitrile in water fraction (v/v) on a SPE column followed by lyophilisation. By applying ultrasonic treatment to the plant matrix leached in nhexane followed by a single step purification process, 2.74 mg of plumbagin per gram of plant material could be obtained with a recovery of 86.3% and over 99% purity.